Characteristics of Maleo (Macrocephalon maleo) roosting trees in North Buton Wildlife Reserve, Southeast Sulawesi, Indonesia - KEMAL MUHSANDI; JARWADI BUDI HERNOWO; YUDI SETIAWAN (Society for Indonesian Biodiversity, 2025)
Abstract. Muhsandi K, Hernowo JB, Setiawan Y. 2025. Characteristics of Maleo (Macrocephalon maleo) roosting trees in North Buton Wildlife Reserve, Southeast Sulawesi, Indonesia. Biodiversitas 26: 3030-3039. Maleo (Macrocephalon maleo) exhibits a high degree of selectivity in choosing roosting trees, a behavior influenced by the availability and specific characteristics that ensure safety and comfort. This study was conducted in the North Buton Wildlife Reserve, Southeast Sulawesi, Indonesia, a conservation area known for its Maleo population, and focused on examining the attributes of roosting trees. A purposive sampling method was employed to identify Maleo roosting trees, and a single-plot method was used for vegetation analysis to determine the composition and structure of surrounding tree species using the Importance Value Index (IVI). The characteristics of roosting trees were analyzed based on several parameters, including total tree height, Diameter at Breast Height (DBH), crown architecture, branching structure, roost height and position, and proximity to food sources and nesting grounds. Wilcoxon rank-sum tests compared tree height and DBH between roosted and non-roosted trees. The results indicated that Maleo roost trees are emergent trees, taller than surrounding vegetation, spatially isolated, and characterized by open crowns with widely spaced, relatively flat branches. Horizontally, Maleos typically roost at the center of the tree crown; vertically, their roosting position is far from the main trunk, reducing disturbance. Roosting trees near food sources and nesting grounds reflect efficient habitat utilization. This efficient spatial utilization of the Maleo bird is a testament to its adaptability and is truly admirable.